STUDI LITERATUR: TRANSFORMASI MANAJEMEN PEMBELAJARAN ANAK TUNAGRAHITA DI SEKOLAH LUAR BIASA - Mutia Fitri Yana; Praja Tuala, Riyuzen; Fradito, Aditia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is designed to conduct a systematic review of the transformation of study management for children who have disabilities in Unique schools (SLB) To optimize the efficiency and effectiveness of education for children requiring special support. This research methodology deployed is Systematic Literature Review (SLR) to collect, evaluate, and analyze data from various sources related to learning management for children with disabilities. The results show that careful planning, effective organization and responsive implementation are essential in creating an inclusive Learning atmosphere conducive to children's development with disabilities.